2013
DOI: 10.1111/bph.12196
|View full text |Cite
|
Sign up to set email alerts
|

IL‐22 in tissue‐protective therapy

Abstract: IL‐22, a member of the IL‐10 cytokine family, has recently gained significant attention as a protective agent in murine models of diseases driven by epithelial injury. Like its biochemical and functional sibling IL‐10, IL‐22 elicits cellular activation primarily by engaging the STAT3 signalling pathway. Exclusively produced by leukocytes, but targeting mostly cells of epithelial origin, IL‐22 has been proposed as a specialized cytokine messenger acting between leukocytic and non‐leukocytic cell compartments. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 140 publications
(195 reference statements)
0
56
0
1
Order By: Relevance
“…5 Recombinant IL-22 is currently under development for the treatment of acute liver failure (Generon Corporation, Shanghai, China). In the current study, we provide in vivo evidence for the first time that administration of recombinant IL-22 or overexpression of IL-22 by injection of Ad-IL-22 or gene targeting ameliorates renal I/R injury and preserves renal functions by activating STAT3 and AKT in the proximal tubular epithelial cells (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Recombinant IL-22 is currently under development for the treatment of acute liver failure (Generon Corporation, Shanghai, China). In the current study, we provide in vivo evidence for the first time that administration of recombinant IL-22 or overexpression of IL-22 by injection of Ad-IL-22 or gene targeting ameliorates renal I/R injury and preserves renal functions by activating STAT3 and AKT in the proximal tubular epithelial cells (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…5 Particularly, the hepatoprotective effects of IL-22 have been extensively investigated. It has been shown that administration of recombinant IL-22 significantly alleviates murine hepatic injury in response to concanavalin A, alcohol, acetaminophen, I/R, or other insults by ameliorating hepatocyte damage (reviewed in ref.…”
Section: Il-22 Treatment Ameliorates Renal I/r Injury By Activating Smentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacologic use of cytokines that act in protective manner on parenchyma tissues, such as IL-10 114 , IL-22 115 or EGF-like factors, such as amphiregulin 15 , were also used promote disease tolerance to infections in mice.…”
Section: Pharmacological Modulation Of Disease Tolerancementioning
confidence: 99%